Clinico-pathological evaluation and co-morbidities in superior mesenteric artery thrombosis - Shukla, Snehil; Singh, Urvashi; Patel, Badri Prasad; ., Vignesh (International Surgery Journal, 2022)
Background: Mesenteric artery thrombosis (MAT) is a condition involving occlusion of the arterial vascular supply of the intestinal system. It is a severe and potentially fatal illness typically of the superior mesenteric artery (SMA), which provides the primary arterial supply to the small intestine and ascending colon. The occlusion may occur due to underlying atherosclerotic disease or embolic occlusion from a distant source, as atrial fibrillation. The condition possesses a high mortality rate and prompt recognition and treatment are of utmost importance. Methods: A retrospective, observational, single hospital base study done during the period from 2015 to 2020 in the department of surgery, Gandhi Medical College, Bhopal. Sample size was taken 50 patients. Results: In our study, out of 50 patients, 34% patients were in the age group between 55-65 years, history of smoking was present in 44%, hypertension in 36%, past history of atrial fibrillation in 10%, signs of peritonitis were present in 62% patients. Out of 50 patients, 42% was operated while 58% were managed conservatively. Amongst operated patients, in 72% partial bowel resection was done while in 28% extensive bowel resection was done, 66% were discharged while 28% patients died, amongst 21 operated patients, 57% were discharged while 43% died. Conclusions: In this study, SMA thrombosis is more common in patients with smoking, cardiac diseases (hypertension, atrial fibrillation, ischemic heart disease, CVA), dyslipidaemia. Early intervention as thrombolysis or bypass surgery is needed to prevent complications like extensive bowel ischemia.